SILABI ANALISIS TATA KELOLA TEKNOLOGI INFORMASI LAYANAN SISTEM INFORMASI AKADEMIK UNIVERSITAS RIAU MENGGUNAKAN KERANGKA KERJA COBIT - Mulyana, Refni; Anugerah, Rita (Jurnal Akuntansi (Media Riset Akuntansi & Keuangan), 2015)
For improvement of Service College, the University of Riau has been usingacademic information systems. Academic information system has the advantage tooptimize the administration and its resources, such as faculty, classes, and a meansof learning. To gain optimal benefit, required good governance of informationsystems. The purpose of this study was to look at the maturity of informationtechnology governance in Riau University by COBIT framework. Domains that arediscussed in this study are the planning, implementation, and evaluation of theinformation system of the University of Riau. This research was conducted usingqualitative methods in the form of case studies. Data on governance Riau Universitywill be compared with the COBIT framework, in order to know the level of maturity.Results of the study is the maturity level of information technology governance at theUniversity of Riau for the three domains studied, namely the domain of planning,implementation, and evaluation at the level 2 (repetition intuitive). This shows thatthe three domains has been implemented, even though not yet well defined (level 3-has been defined).Keywords: information technology governance, academic information systems,COBIT